2015
DOI: 10.3122/jabfm.2015.05.140332
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decisions Made in Primary Care Clinics Before and After Choosing Wisely 

Abstract: Background:The Choosing Wisely ™ campaign encourages physicians to avoid low-value care. Although widely lauded, no study has examined its impact on clinical decisions made in primary care settings.Methods: We compared clinical decisions made for 5 Choosing Wisely recommendations over two 6-month time periods before and after the campaign launch and an educational intervention to promote it at 3 primary care residency clinics.Results: The rate of recommendations adherence was high (93.2%) at baseline but did s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 6 publications
(3 reference statements)
1
26
0
Order By: Relevance
“…19 There may, however, be greater hope for the success of interventions at a practice level. Kost et al 20 recently reported their interventions in 3 primary care residency programs. They educated providers about Choosing Wisely clinical behaviors and formulated instruction about a "step wise approach to communicating to patients a plan of care based on the recommendations."…”
Section: Barriers To Guideline-concordant Carementioning
confidence: 99%
See 1 more Smart Citation
“…19 There may, however, be greater hope for the success of interventions at a practice level. Kost et al 20 recently reported their interventions in 3 primary care residency programs. They educated providers about Choosing Wisely clinical behaviors and formulated instruction about a "step wise approach to communicating to patients a plan of care based on the recommendations."…”
Section: Barriers To Guideline-concordant Carementioning
confidence: 99%
“…In particular, greater adherence to osteoporosis screening and sinusitis treatment recommendations were noted. 20 …”
Section: Barriers To Guideline-concordant Carementioning
confidence: 99%
“…[25][26][27][28] However, three population-level analyses of insurance claims show mixed results. 3,4,29 Experts have thus proposed using implementation science to improve uptake of CW recommendations. 2,3,7,8 Our study demonstrates the effectiveness of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…1 They concluded that "primary care physicians respond to training and publicity in low-value care." This intervention strategy decreased physician-initiated testing that provide little clinical value.…”
Section: Re: Clinical Decisions Made In Primary Care Clinics Before Amentioning
confidence: 99%